Meals for the dead: the image of the deceased seated before a table of offerings - Robins, G (2010)
One of the most frequent images found on ancient Egyptian funerary monuments is the image of the deceased seated before a table of offerings including food and drink. It appears as early as the slab stelae of the Second Dynasty. In the Old Kingdom, it occurs on false door stelae and it remains the main image found on Middle Kingdom funerary stelae, where it is usually combined with a standard offering formula. In this paper, I show that the superficially simple image of the deceased seated before a table of offerings is very complex, with multiple layers of meaning that may have increased over time, as offered items acquired secondary symbolic interpretations. In the offering formula, the offerings are said to be for the recipient’s kA, creating a pun between the word kAw “nourishment” and kA, the animating life force of family lineages from ancestors to the new-born and thus shared by the living and the transformed dead, who are those who have successfully passed through death to the next stage of life. Offerings depicted do not include the range of food available to ancient Egyptians. The basic offering formula asks for bread, beer, beef, and birds. Bread and beer, made from grain, were staples, but beer was also associated with the goddess Hathor, mistress of drunkenness, who was connected with fertility and birth and by extension regeneration and rebirth into the afterlife. The foreleg played a central role in the animating Opening of the Mouth ritual, when the life force of the bull was transferred to the deceased, in a pun on the word kA “bull”. Migratory birds, such as the pintail duck, came from the realm of chaos outside the ordered world of Egypt and thus their slaughter indicated victory over chaos, which in a funerary setting could be understood as victory over the chaos of death. Possible symbolic meanings, whether original or secondary, can also be suggested for other items that appear as common offerings. The image, therefore, goes beyond a simple meal for the dead to embody notions of status and identity, the successful passage of the deceased into the next life, his continued maintenance there by the living, and the on-going interaction of the living and the dead through ritual performance.